THE ROLE OF IRRIGATION MANAGEMENT IN INCREASING RICE PRODUCTION IN SOUTH KOREA - NGURAH SANTOSA, I GUSTI; JAEWOO, CHANG (Agrotrop : Journal on Agriculture Science; Vol 1 No 1 (2011))
Increasing of rice production is one of a highlight program in South Korea. In order to support this, enough water supply for paddy field is one of determined main factors to maintain good plant growth and high yield. Water from the rainfall is usually not enough for paddy field, so it must be supplied from irrigation system. The water source for irrigation can be derived from surface water and or ground water which is usually located in long distance, consequently it needs irrigation facilities to deliver water until reach paddy field area. Therefore government, and, or farmer need to manage irrigation to fulfill paddy field water requirement and they have been doing it. By working hard and holding strong commitment, South Korea has been reaching rice self sufficiency average 98,9% since 1970s for 38 years period. Average rice yield was 5.20 ton per ha in 2008 and this indicates as the highest level of rice yield in the world as well. Based on this reality, it needs to be studied the role of irrigation management in increasing rice production in South Korea. It was found that irrigation management in South Korea has very important role and it has significant effect in increasing rice production. This reality was supported by increasing of safety paddy field area by year. The water potential developed and to be developed is higher than water use. Government provided K Water (Korea Water Resources Cooperation) to handle everything in relation to water problem.
Keywords: irrigation management, rice production, South Korea